2012
DOI: 10.1007/s10529-012-0951-2
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of stress protein-encoding genes helps Clostridium acetobutylicum to rapidly adapt to butanol stress

Abstract: The toxicity of n-butanol in microbial fermentations limits its formation. The stress response of Clostridium acetobutylicum involves various stress proteins and therefore, over-expression of genes encoding stress proteins constitutes an option to improve solvent tolerance. Over-expression of groESL, grpE and htpG, significantly improved butanol tolerance of C. acetobutylicum. Whereas the wild type and vector control strain did not survive 2 % (v/v) butanol for 2 h, the recombinant strains showed 45 % (groESL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…The gene Cthe_0550 is annotated as encoding Hsp90 and was up regulated after all stress treatment (Additional file 1: Table S1). Overexpression of htpG was recently shown to enhance butanol tolerance and eventual strain adaptation to butanol in C. acetobutylicum [45] and could provide a route for enhanced solvent resistance in C. thermocellum. …”
Section: Discussionmentioning
confidence: 99%
“…The gene Cthe_0550 is annotated as encoding Hsp90 and was up regulated after all stress treatment (Additional file 1: Table S1). Overexpression of htpG was recently shown to enhance butanol tolerance and eventual strain adaptation to butanol in C. acetobutylicum [45] and could provide a route for enhanced solvent resistance in C. thermocellum. …”
Section: Discussionmentioning
confidence: 99%
“…Organic solvents cause protein damage leading to misfolding. It has been demonstrated that overexpression of heat shock proteins, such as the GroESL system in Clostridium acetobutylicum (a butanol-producing bacteria), results in improved solvent tolerance and solvent production (132). HSP genes can be found in a broad range of antibiotic-resistant plasmids from the Enterobacteriaceae family and in plasmids involved in rhizobia-plant symbiosis.…”
Section: Plasmids Involved In Solvent/aromatic Compound Tolerancementioning
confidence: 99%
“…With the increasing supply of fossil fuel resources and continuous improvements in environmental protection awareness, the production of biofuels from renewable raw materials has become a global priority. Butanol is considered a potential new alternative biofuel and its production through fermentation has received renewed interest in recent years . At present, the genus Clostridium including C. acetobutylicum and C. beijerinckii has been extensively studied for its specific ability to biosynthesize alcohols (butanol and ethanol) and acetone.…”
Section: Introductionmentioning
confidence: 99%